Electrospun polysaccharide scaffolds: wound healing and stem cell differentiation. Issue 7 (3rd May 2022) - G. U., Preethi; B. S., Unnikrishnan; J., Sreekutty; M. G., Archana; Mohan, Deepa; Pillai K., Raveendran; T. T., Sreelekha
Abstract: Irrespective of the labyrinth of fastidiously woven artificial scaffolds, the lack of biocompatibility hampers effective clinical translation, which is the definitive purpose of any biomedical system or device. Hence, the current exploration deals with the fabrication of scaffolds with enhanced bioactivities for wound healing. The methodology used for the fabrication of the scaffolds was electrospinning of the polysaccharide, which is isolated from tamarind seed kernel using the electrospinning process. To improve the antimicrobial activity of the scaffolds, in-house synthesized silver nanoparticles were added to the scaffolds. Wound healing and antimicrobial efficiency of the scaffolds were established in murine models. An insight into the wound healing mechanism was also analyzed using differentiation screening of stem cells grown on scaffolds. The results showed that newly synthesized scaffolds presented excellent wound healing ability along with antimicrobial activity. Furthermore, detailed toxicological evaluations through the histopathology and collagen staining wound sections, the probability of any off-target effects were also ruled out. Differentiation screening showed that adipogenesis was more prominent in cells attached to the scaffolds and markers of adipogenesis were strongly expressed in fluorescent microscopy. Thus we hope that the scaffolds mediate stem cell differentiation in wounds and promote a progressive healing response. Results thus obtained were encouraging and further studies need to embark on to establish the combined role in all aspects studied here.